Sexual dysfunction prevalence, risk factors, and help-seeking behavior in opioid agonist treatment and general psychiatry: a cross-sectional study - Meyer, Maximilian; Westenberg, Jean N.; Brunner, Patrick; Gürtler, Martin; Wiesbeck, Gerhard A.; Lang, Undine E.; Vogel, Marc; Dürsteler, Kenneth M. (Frontiers in Psychiatry, 2023)
Background: Mental disorders pose a high risk for the occurrence of sexual dysfunctions (SD). This study aimed to investigate prevalence of risk factors and help-seeking behaviour for sexual dysfunctions in patients with opioid use disorder compared to patients seeking psychotherapeutic help.Methods: Ninety-seven patients at two opioid agonist treatment (OAT) centres and 65 psychotherapeutic patients from a psychiatric practice (PP) in Switzerland were included in the study. Self-report assessments comprised sexual functioning (IIEF: International Index of Erectile Function; FSFI: Female Sexual Function Index), depressive state, psychological distress, alcohol consumption, nicotine use, and a self-designed questionnaire on help-seeking behaviour. We used chi-squared and Mann-Whitney U tests for group comparisons and binary logistic regression models to identify variables predicting the occurrence of sexual dysfunctions.Results: There was no statistically significant difference (p=.140) in the prevalence of SD between OAT (n=64, 66.0%) and PP sample (n=35, 53.8%). OAT patients scored significantly higher in scales assessing nicotine use (p<.001) and depressive state (p=.005). Male OAT patients scored significantly worse on the Erectile Function scale (p=.005) and female PP patients scored significantly worse on the FSFI Pain domain (p=.022). Opioid use disorder, higher age, and being female predicted the occurrence of SD in the total sample. In the OAT sample, only higher age remained predictive for the occurrence of SD. A lack of help-seeking behaviour was observed in both groups, with only 31% of OAT patients and 35% of PP patients ever having talked about their sexual health with their treating physician. This is a provisional file, not the final typeset article Conclusion: SD are common among psychiatric patients receiving OAT and general psychiatric patients seeking psychotherapy. Professionals providing mental healthcare to patients must emphasise prevention and routine assessments of sexual functioning needs.